The incidence of insurance on economic growth in Italy, France, United Kingdom and Romania - Bianca Costache (Financial Studies, 2018)
This research paper is focused on an important topic in the economic literature, more precisely how the insurance sector impacts the overall economic growth. The objective of the study is to identify, analyse and evaluate the effects of the insurance sector on economic growth for three countries: France, United Kingdom and Italy, with data collected for the period 1984-2016 and also for Romania with data for 2008 - 2017. The results of the study proved to be important as they indicate the variation in the effects of insurance instruments due to the peculiarity of each economy and the way in which each economy responds to a positive impact from the insurance sector.
Keywords: C32; G220; O410; 330; DP; gross written premiums; cointegration; causality